Anti-diabetic activity and Nuclear Magnetic Resonance (NMR) characterization of natural esters from hexane and dichloromethane crude extracts from calyces of hibiscus sabdariffa linn - Mohd Azlan Nafiah (Tanjong Malim, 2019)
Anti-diabetic activity and Nuclear Magnetic Resonance (NMR) characterization of natural esters from hexane and dichloromethane crude extracts from calyces of hibiscus sabdariffa linn by Mohd Azlan Nafiah